2018
DOI: 10.3390/v10030119
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effects of ABMA against Herpes Simplex Virus Type 2 In Vitro and In Vivo

Abstract: Herpes simplex virus type 2 (HSV-2) is the causative pathogen of genital herpes and is closely associated with the occurrence of cervical cancer and human immunodeficiency virus (HIV) infection. The absence of an effective vaccine and the emergence of drug resistance to commonly used nucleoside analogs emphasize the urgent need for alternative antivirals against HSV-2. Recently, ABMA [1-adamantyl (5-bromo-2-methoxybenzyl) amine] has been demonstrated to be an inhibitor of several pathogens exploiting host-vesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
(87 reference statements)
0
29
0
Order By: Relevance
“…These drugs inhibit the viral DNA polymerase via triphosphorylation, affecting viral replication (Benzekri et al, 2018). However, drug resistance rates are increasing, especially among immunosuppressed individuals (Dai et al, 2018). There is currently no effective HSV-2 vaccine (Churqui et al, 2018), so the exploration of natural plant pharmaceuticals and their active components has become .…”
Section: Discussionmentioning
confidence: 99%
“…These drugs inhibit the viral DNA polymerase via triphosphorylation, affecting viral replication (Benzekri et al, 2018). However, drug resistance rates are increasing, especially among immunosuppressed individuals (Dai et al, 2018). There is currently no effective HSV-2 vaccine (Churqui et al, 2018), so the exploration of natural plant pharmaceuticals and their active components has become .…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus type‐2 is a causative pathogen of genital herpes and is closely associated with HIV infection . Here, we found that trilobatin at high concentrations (458 μ m ) was also effective in inhibiting HSV‐2 infection, suggesting that this compound may also be applicable in those coinfected patients (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Replication of the distantly related respiratory syncytial virus, for instance, is potently blocked by the small-molecule compound RSV604 that is considered to interfere with P-RNP binding [134]. Structural models of RNP and the C-terminal domain of P proteins of both RABV and MOKV revealed close structural homology and interaction mechanism similar to these employed by the related paramyxo-and pneumoviruses [99,[135][136][137][138]. Through yeast-2-hybrid screening, several peptides were identified that bind directly to both RABV and MOKV P in highly conserved regions, inhibiting viral replication in minigenome assays.…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…A similar dynamin inhibitor, AMBA, has also shown antiviral effects against HSV, but the selectivity index (SI = CC 50 /EC 50 ) was at a low <21. When tested in vivo, there was only a 50% survival rate of mice given a lethal RABV challenge, greatly compromising therapeutic potential against the RABV indication [99]. Since AMBA was a direct hit compound from a high-throughput screen, synthetic optimization to improve efficacy was suggested.…”
Section: Host-directed Rabv Inhibitorsmentioning
confidence: 99%